Evaluation of a continuous glucose monitoring system in neonatal foals. (6th June 2021) - Wong, David; Malik, Caitlin; Dembek, Katarzyna; Estell, Krista; Marchitello, Megan; Wilson, Katie
Abstract: Background: Monitoring blood glucose concentrations is common in critically ill neonatal foals, especially septic foals and those receiving naso‐esophageal feedings or IV parenteral nutrition. Glucose typically is measured using a point‐of‐care (POC) glucometer but requires repeated restraint and blood collections, which may cause irritation at venipuncture sites and increased demands on nursing staff. Continuous glucose monitoring systems (CGMS) may provide an accurate alternative for monitoring blood glucose concentration. Objectives: To determine the correlation and accuracy of a CGMS to monitor neonatal foals' blood glucose concentrations as compared to a POC glucometer and laboratory chemistry analysis (CHEM). Animals: Samples from 4 healthy and 4 ill neonatal foals. Methods: A CGMS was placed on each foal, and glucose measurements acquired from this device were compared to simultaneous measurements of blood glucose concentration using a POC glucometer and CHEM. Results: Two‐hundred matched glucose measurements were collected from 8 neonatal foals. The mean bias (95% limits of agreement) between CGMS and CHEM, CGMS and POC glucometer, and POC glucometer and CHEM was 3.97 mg/dL (−32.5 to 40.4), 18.2 mg/dL (−28.8 to 65.2), and 22.18 mg/dL (−9.3 to 53.67), respectively. The Pearson's correlation coefficient (r) was significantly correlated among all devices: GCMS and CHEM (r = 0.81), CGMS and POC glucometer (r = 0.77) and POC glucometer‐CHEM (r = 0.92). Conclusions and Clinical Importance: Within the blood glucose concentration ranges in this study (78‐212 mg/dL), CGMS measurements were significantly correlated with CHEM, suggesting that it is an acceptable method to provide meaningful, immediate, and continuous glucose concentration measurements in neonatal foals while eliminating the need for repeated restraint and blood collection.